2010
DOI: 10.1111/j.1349-7006.2010.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of heme oxygenase‐1 in human leukemic cells and its regulation by transcriptional repressor Bach1

Abstract: Heme oxygenase (HO)-1 has anti-oxidative, anti-inflammatory, and anti-apoptotic activities. However, little is known about the regulation of HO-1 in human primary acute myeloid leukemia (AML) cells. Here we investigated the expression of HO-1 in primary and established AML cells as well as other types of leukemic cells and normal monocytes, and its regulatory mechanism by the transcriptional repressor, BTB and CNC homology 1 (Bach1), and the activator, nuclear factor erythroid-derived 2 related factor 2 (Nrf2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 41 publications
(97 reference statements)
7
53
0
Order By: Relevance
“…Overexpression of miR-155 has been observed in several types of B-cell lymphomas and induces B-cell malignancies in transgenic mice (73). Down-regulation of BACH1 in human acute myeloid leukemia cells decreases the cytotoxic effect of the anticancer drug cytosine arabinoside, rendering functional up-regulation of BACH1 a potential strategy for antileukemic therapy (11). In this respect, we have identified here two noncoding vault RNAs as BACH1 targets whose expression has been linked to Mitoxantrone resistance in human malignant cells (74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of miR-155 has been observed in several types of B-cell lymphomas and induces B-cell malignancies in transgenic mice (73). Down-regulation of BACH1 in human acute myeloid leukemia cells decreases the cytotoxic effect of the anticancer drug cytosine arabinoside, rendering functional up-regulation of BACH1 a potential strategy for antileukemic therapy (11). In this respect, we have identified here two noncoding vault RNAs as BACH1 targets whose expression has been linked to Mitoxantrone resistance in human malignant cells (74).…”
Section: Discussionmentioning
confidence: 99%
“…Among other proteins involved in the heme degradation pathway, HMOX1 and the biliverdin reductases A and B were proposed as serum biomarkers for the early detection of Alzheimer disease (10). Furthermore, BACH1 expression was down-regulated by microRNAs in viral infection-associated cancerogenesis (11)(12)(13).…”
mentioning
confidence: 99%
“…In rodent macrophages, HO-1 has been shown to be up-regulated by lipopolysaccharide (LPS) [21][22][23], which then attenuates the expression of various proinflammatory genes including cyclooxygenase-2, inducible nitric oxide (NO) synthase (iNOS), tumor necrosis factor (TNF)- or interleukin (IL)-6 [18,24] (Figure 1). In contrast to the LPS-dependent induction of HO-1 in rodent macrophages, gene expression of HO-1 is down-regulated by treatment with LPS in human monocytes [25]. More recently, the myeloid cell-specific immunomodulatory functions of HO-1 have also been investigated in a conditional HO-1 knockout mouse model.…”
Section: Myeloid Cellsmentioning
confidence: 99%
“…In addition, HO-1 expression in CLL cells exceeds that in normal lymphocytes. In response to disease or stress, HO-1 expression results in resistance to cell apoptosis and promotes cell proliferation (26). Stuart et al (27) demonstrated that HO-1 was involved in the regulation of leukemia cell apoptosis, proliferation and differentiation through NF-κB, ROS and Nrf2.…”
Section: Discussionmentioning
confidence: 99%